Personality correlates of mindfulness: A study in an Indian setting - Praseeda Menon; Suchitra Doddoli; Sukriti Singh; Ranjit S Bhogal (Wolters Kluwer Medknow Publications, 2014)
Background: Mindfulness has received consistent attention from researchers in the last few decades due to its positive effects on physical and mental health, psychological well-being, as well as several therapeutic outcomes. In an attempt to discern its dispositional source, researchers have also looked at its relation with personality traits. Aims: The current study aims to carry the above effort ahead by looking at the relation of mindfulness to the big-five personality traits in the Indian context in an exploratory way to give some amount of cross-cultural validity to established relations in the Western context. Methods: The current study adopted the method of correlational research to fulfill the above aim. Results: Results of the current investigation on 60 plus Yoga students supported earlier meta-analysis by revealing highly significant moderate correlations, negative of -0.45 with neuroticism and positive of 0.49 with conscientiousness after controlling for demographics. Mindfulness also showed a positive relation to extraversion (r = 0.29), to a lesser extent though. The study, very surprisingly, showed no gender difference in neuroticism in the current sample of Yoga students, thereby creating a deviation to a widely present gender difference. Conclusions: The current paper discusses the above results in detail, and draws the personality mini-profile of a mindful individual to be that of one who is emotionally stable and/or well-disciplined in his/her approach toward life although, studies with larger, representative and cross-cultural samples are needed to further validate this claim.